Russian art 1875 -1975: a collection of essays - Bowlt, John (Austin: University of Texas at Austin, 1976)
Patronage and the neo-nationalist movement: Savra Mamontov and princes Tenisheva -- Synthesism and symbolism: the world of art movement -- The blue rose movement an russian symbolism -- Neo-primitivism and russian painting...
The russian luminist school: the work of Arkhip Kuindzhi --
Keywords: HISTORIA DE LA PINTURA; PINTURA RUSA